Somatic Accumulation of GluA1-AMPA Receptors Leads to Selective Cognitive Impairments in Mice - Bannerman, David M.; Borchardt, Thilo; Jensen, Vidar; Rozov, Andrey; Haj-Yasein, Nadia N.; Burnashev, Nail; Zamanillo, Daniel; Bus, Thorsten; Grube, Isabel; Adelmann, Giselind; Rawlins, J. Nicholas P.; Sprengel, Rolf (Frontiers in Molecular Neuroscience, 2018)
The GluA1 subunit of the L-α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptor (AMPAR) plays a crucial, but highly selective, role in cognitive function. Here we analyzed AMPAR expression, AMPAR distribution and spatial learning in mice (Gria1R/R), expressing the ‘trafficking compromised’ GluA1(Q600R) point mutation. Our analysis revealed somatic accumulation and reduction of GluA1(Q600R) and GluA2, but only slightly reduced CA1 synaptic localization in hippocampi of adult Gria1R/R mice. These immunhistological changes were accompanied by a strong reduction of somatic AMPAR currents in CA1, and a reduction of plasticity (STP and LTP) in the CA1 subfield following tetanic and theta-burst stimulation. Nevertheless, spatial reference memory acquisition in the Morris water-maze and on an appetitive Y-maze task was unaffected in Gria1R/R mice. In contrast, spatial working/short-term memory during both spontaneous and rewarded alternation tasks was dramatically impaired. These findings identify the GluA1(Q600R) mutation as a loss of function mutation that provides independent evidence for the selective role of GluA1 in the expression of short-term memory.